Tanging Yaman - Guillen, Laurice (2001)
Three siblings are now well settled with their respective families, in widely contrasting lifestyles. The one common thing that binds them loosely together is the love that their mother holds for all of them and her grandchildren , albeit expressed in varying ways and degrees, but always equally nurturing and self-giving. Much as they are held together by her, they are in turn separated by physical distance and the sad legacy left behind by their deceased, erstwhile strong-willed, patriarchal father. Long-suppressed pains and resentments unravel as the three siblings argue over the prospect of selling a vast tract of land left behind by the patriarch. The process also brings to surface the hurts between parents and children, a likely spectacle of the "sins of the father visiting upon the children", threatening to spill over to the third generation. Waht stuff each one is made of faces its true test when the family matriarch, in an act richly resonant with ritual Christian self-offrialism, and an unforgiving heart.